The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12030804
|View full text |Cite
|
Sign up to set email alerts
|

From School to Work: Improving Graduates’ Career Decision-Making Self-Efficacy

Abstract: As boundaryless careers become mainstream, individuals need to enhance career decision-making self-efficacy (CDSE) during career transitions to secure better employment outcomes and sustainable career development, especially when moving from a school to a work environment. Drawing on social cognitive career theory, this study empirically proposed a moderated mediation model to examine whether proactive personality (measured at Time 1), career success criteria clarity (CSCC, measured at Time 2), and family soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 75 publications
0
31
0
Order By: Relevance
“…CDMSE can be defined as an individual's belief or confidence that they can make appropriate decisions related to their career development, and it has five dimensions: self-appraisal, gathering information, goal selection, planning, and problem-solving [25]. In various studies, CDMSE served as a crucial factor of an individual's vocational behaviors and outcomes [26][27][28][29], and these findings demonstrate a link between sustainable career development and CDMSE. A meta-analysis showed a positive relationship between CDMSE and career development and a negative relationship between CDMSE and career indecision [30].…”
Section: Career Decision-making Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…CDMSE can be defined as an individual's belief or confidence that they can make appropriate decisions related to their career development, and it has five dimensions: self-appraisal, gathering information, goal selection, planning, and problem-solving [25]. In various studies, CDMSE served as a crucial factor of an individual's vocational behaviors and outcomes [26][27][28][29], and these findings demonstrate a link between sustainable career development and CDMSE. A meta-analysis showed a positive relationship between CDMSE and career development and a negative relationship between CDMSE and career indecision [30].…”
Section: Career Decision-making Self-efficacymentioning
confidence: 99%
“…According to Lent, personal and contextual factors affect CDMSE in a complexly interactive way [13]. For instance, given that a proactive personality positively predicts CDMSE, career educators could explore high-school students' difficulties in developing CDMSE by measuring this trait [26]. On the other hand, perceived support from influential and important people (e.g., family members) is likely to have more impact on CDMSE than other contextual factors, and this impact is more significant during adolescence [73]; therefore, it is essential to construct a bridge between high schools and parents, and high schools must strengthen parents' awareness about their children's sustainable career development rather than academic scores.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For career decision-making, it is proved that the career decisionmaking difficulties of college students are negatively predicted by proactive personality (He et al, 2020). Xin et al (2020) suggested that a strong proactive personality plays a prominent role in career success criteria, and individuals with strong proactive personalities have more confidence in making career decisions.…”
Section: Related Workmentioning
confidence: 99%
“…Different from other career paradigms, the sustainable career perspective focuses explicitly and intensively on individual and contextual factors related to career management [6]. Entrepreneurial career decisions, particularly for the formation of entrepreneurial career intention, are emerging and important issues in sustainable career development research and practice [2,3,[7][8][9][10]. Entrepreneurial career intention refers to the intention to pursue a career in entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%